2001
DOI: 10.1097/00000658-200101000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Cachexia: Current Concepts of Intracellular Mechanisms and Molecular Regulation

Abstract: ObjectiveTo review present knowledge of intracellular mechanisms and molecular regulation of muscle cachexia. Summary Background DataMuscle cachexia, mainly reflecting degradation of myofibrillar proteins, is an important clinical feature in patients with severe injury, sepsis, and cancer. The catabolic response in skeletal muscle may result in muscle wasting and weakness, delaying or preventing ambulation and rehabilitation in these patients and increasing the risk for pulmonary complications. ResultsMuscle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
156
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(161 citation statements)
references
References 67 publications
4
156
0
1
Order By: Relevance
“…Interestingly, the double treatment also decreased m‐calpain gene expression, known to play a role in muscle proteolysis in cancer cachexia 43, 44. Indeed, it was suggested that calcium‐dependent proteases participate in the release of myofilaments from the sarcomere, and these myofilaments would be later degraded by the ubiquitin‐dependent proteolytic system 45. Sandri et al reported the role for lysosome activity in muscle degradation during cancer cachexia.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the double treatment also decreased m‐calpain gene expression, known to play a role in muscle proteolysis in cancer cachexia 43, 44. Indeed, it was suggested that calcium‐dependent proteases participate in the release of myofilaments from the sarcomere, and these myofilaments would be later degraded by the ubiquitin‐dependent proteolytic system 45. Sandri et al reported the role for lysosome activity in muscle degradation during cancer cachexia.…”
Section: Resultsmentioning
confidence: 99%
“…These two processes have been suggested to contribute less than 15 -20% towards total protein breakdown in muscle (Attaix et al, 1998;Lecker et al, 1999) and do not breakdown myofibrillar proteins (Lovell et al, 1986). However, the calcium/calpain pathway has been suggested to release myofilaments from the sarcomere in an early and perhaps rate-limiting component of the catabolic response in muscle (Hasselgren and Fischer, 2001). Further catabolism of the actin and myosin released from the myofilaments is considered to occur via the ubiquitin-proteasome proteolytic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Protein hypercatabolism and muscle wasting characterize catabolic states induced by sepsis and trauma (Hasselgren & Fischer 2001). The mechanisms responsible for these changes have not been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%